2016
DOI: 10.1007/s11199-016-0669-z
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of Physics as a Quintessentially Masculine Subject: Young People’s Perceptions of Gender Issues in Access to Physics

Abstract: The present article investigates explanations for gendered trends in Physics and Engineering access, reporting findings from a large-scale study funded by the UK Economic and Social Research Council and drawing primarily on data from interviews with 132 15–16 year-old adolescents and their parents. Survey results in our study and elsewhere show strong gender disparities in anticipated pursuit of Physics after completion of compulsory education. In order to explore the constructions of gender and Physics underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 53 publications
4
58
0
Order By: Relevance
“…It's a totally different way of learning, really. They also express a strong focus on assessment, tests, and exams in line with the implied student of the traditional physics classroom (Carlone, ; Yerdelen‐Damar & Elby, ). A quote from one student illustrates how the cleverness and importance of achievement is part of what identifies them as physics students (Francis et al., ; Taconis & Kessels, ).
But we, who take physics, we want to get good grades.
They appear to be socialized into a culture oriented toward test outcomes and final qualifications.…”
Section: Resultsmentioning
confidence: 99%
“…It's a totally different way of learning, really. They also express a strong focus on assessment, tests, and exams in line with the implied student of the traditional physics classroom (Carlone, ; Yerdelen‐Damar & Elby, ). A quote from one student illustrates how the cleverness and importance of achievement is part of what identifies them as physics students (Francis et al., ; Taconis & Kessels, ).
But we, who take physics, we want to get good grades.
They appear to be socialized into a culture oriented toward test outcomes and final qualifications.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, here again the situation is complex. Francis et al (2016) show that issues of (lack of) representation of women in physics, and the continuing incidents of discrimination in the physics workplace which girls use as allegorical tales to illustrate the hostility of the profession to women, also have a strong impact on girls' disassociation from physics. It is important, then, not to simply responsibilise (see Rose 1999) girls for their 'failure' .…”
Section: Femininity and Engagement With Stemmentioning
confidence: 95%
“…The association of science careers with masculinity has also been shown to be off-putting for some girls (Archer et al 2012a(Archer et al , 2012b, with children perceiving science as being 'for boys' (Calabrese Barton and Tan 2009;Caleon and Subramaniam 2008;Carlone 2003;Farenga and Joyce 1999;Francis 2000b;Fennema and Peterson 1985). Especially, the construction of physics as 'quintessentially masculine' (Francis et al 2016) has been shown to impede engagement for many girls, due to the lack of 'fit' of this symbolically masculinised subject with their identification with femininity (see Gonsalves 2014;Archer et al forthcoming).…”
Section: Femininity and Engagement With Stemmentioning
confidence: 99%
“…Second, variation in subject choice by social class and gender has been explained by students' taken-for-granted sense of what is 'normal' for people like them (e.g. Francis et al, 2017). This portrayal of social and gender identity reproduction generates two views of critical information.…”
Section: Alternative Perspectives On Subject Choice-implications For mentioning
confidence: 99%